LifePearl microspheres loaded with irinotecan in the treatment of Liver-dominant metastatic colorectal carcinoma: feasibility, safety and pharmacokinetic study. Issue 10 (November 2020) - Maleux, Geert; Prenen, Hans; Helmberger, Thomas; Spriet, Isabelle; Isailovic, Tatjana(V); Pereira, Philippe
Abstract : To evaluate pharmacokinetic and safety profile of LifePearl microspheres loaded with irinotecan (LifePearl-IRI) in the treatment of liver-dominant, metastatic colorectal carcinoma (LM-CRC) by transarterial chemoembolization. In a prospective, multicentre pharmacokinetic study, 14 patients with LM-CRC progressing on at least one line of chemotherapy were treated with LifePearl-IRI. Six patients received unilobar treatment, treating one lobe per session with 100 mg of irinotecan every 2 weeks. Eight patients received bilobar treatment, treating two lobes per session with 100 mg of irinotecan each (200 mg in total), every 4 weeks. At 24 h, near complete plasma clearance occurred for both irinotecan and SN-38, regardless of the dose. Mean plasma Cmax(100 mg) was 254.50 ± 104.17 ng/mL for irinotecan and 46.72 ± 13.75 ng/mL for SN-38. Mean Cmax(200 mg) was 970.09 ± 353.75 ng/mL for irinotecan and 118.45 ± 25.11 ng/mL for SN-38. Significantly higher Cmax-iri(200 mg) than Cmax-iri (100 mg) supported rate-limiting irinotecan-to-SN-38 conversion. Adverse events during the first 30 days upon initial treatment were hypertension in 21.4%, abdominal pain in 14.3%, and increased transaminases and fever in 7.1% of patients. Four serious adverse events were noted: respiratory failure, constipation, necrotizing pancreatitis, and ischaemic cholecystitis. Chemoembolization with LifePearl-IRI is technically feasible and relatively well tolerated, with a good pharmacokinetic profile and minimal systemic exposure of both irinotecan and SN-38, after both unilobar and bilobar treatment with 100 or 200 mg, respectively.